Humus balance and nutrient regime of irrigated soil under different systems of primary soil tillage and fertilization - Maliarchuk , M. P.; Maliarchuk, A. S.; Tomnitskiy, A. V. (AgroChemistry and Soil Science, 2022)
The article presents an analysis of the results of experimental research in a stationary field experiment to determine the peculiarities of the formation of humus reserves and the nutrient regime in the arable layer of the dark chestnut soil (Haplic Kastanozem) under the influence of different fertilization and main cultivation systems. The purpose of the research: to establish the patterns of transformation of by-products of agricultural crops of crop rotation into humus and the main elements of mineral nutrition of plants under organic and two organo-mineral fertilization systems against the background of five systems of main cultivation in a 4-field row crop rotation on irrigated lands in the area of operation of the Ingulets irrigation plant systems. The research was conducted in the stationary experiment of the Institute of Irrigated Agriculture of the National Academy of Sciences in the Kherson region of Ukraine during 2016-2020. The following indicators were used to analyze the effectiveness of the combined application of fertilization systems and the main tillage: mass of post-harvest residues for each of the crop rotations; stocks of humus in the arable layer; humus balance; the mass of nitrogen, phosphorus and potassium that reached the soil with plant residues; ecological and economic effect (UAH/ha); energy gain (GJ/ha). As a result of experimental studies, it was found that the formation of humus reserves in the soil depends on the mass of post-harvest residues of crop rotation and the methods and depth of their wrapping. The most favorable conditions for the accumulation of leaf-stem mass of crop rotation crops and the formation of a positive balance of humus with an average annual increase of 2.02 t/ha were provided by the organo-mineral fertilization system using the by-products of crop rotation crops and a dose of mineral fertilizers N120P60 against the background of differentiated main cultivation with one slotting to a depth of 38-40 cm per rotation.